2023
DOI: 10.1111/ajco.13949
|View full text |Cite
|
Sign up to set email alerts
|

Impact of neoadjuvant systemic chemotherapy followed by cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for appendiceal adenocarcinoma

Abstract: AimPeritoneal dissemination of infiltrative appendiceal tumors is a rare and poorly understood phenomenon. Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) is a well‐recognized treatment option for selected patients. Neoadjuvant systemic chemotherapy (NAC) has been shown to be associated with improved overall survival (OS) in colorectal peritoneal metastases but little is known of the impact of this from an appendiceal adenocarcinoma perspective.MethodA prospective database of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The role of radiotherapy in ASCA is uncertain. For appendiceal tumor spreading to peritoneum, cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) are considered the standard treatments 21 . Yet, it remains controversial in peritoneal dissemination from signet-ring cell carcinoma from the appendix 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of radiotherapy in ASCA is uncertain. For appendiceal tumor spreading to peritoneum, cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) are considered the standard treatments 21 . Yet, it remains controversial in peritoneal dissemination from signet-ring cell carcinoma from the appendix 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes were overall and disease-free survival, and adverse events. Seventeen studies reported on preoperative or neoadjuvant chemotherapy ( [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] ), 6 reported on postoperative or adjuvant chemotherapy ( [47][48][49][50][51] ), 9 reported on both ( [52][53][54][55][56][57][58][59][60] ), and 2 reported on other or unspecified regimens ( 61,62 ). These studies are summarized in Table 2, addressed qualitatively in Principles of Systemic Therapy, and applied in blocks 3 and 6 of the Appendiceal Adenocarcinoma pathway.…”
Section: Rapid Reviewmentioning
confidence: 99%
“…48,53,54,59,60,[71][72][73]78 Others studies have shown minimal benefit or even detriment after adjuvant therapy; it is unclear how much of this variation reflects selection bias, as the patients who are most likely to undergo adjuvant therapy are those who are well enough to do so. 47,49,51,52,56 To our knowledge, no studies have comprehensively evaluated the role of modern neoadjuvant therapy for resectable appendix tumors without peritoneal involvement; at present expert consensus opinion is not in favor of neoadjuvant therapy in that setting, as it would delay definitive resection.…”
Section: Cytotoxic Chemotherapy For Localized Appendix Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of adjuvant radiotherapy in appendiceal adenocarcinoma, particularly in ASRCC, is uncertain. Systemic chemotherapy is a viable option for patients with metastatic disease, while cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) are the standard treatments for peritoneal dissemination from appendiceal cancer [36,37]. However, the benefit of CRS/HIPEC in cases of peritoneal dissemination from ASRCC remains controversial [38].…”
Section: Appendiceal Signet Ring Cell Carcinoma: Heterogeneous Presen...mentioning
confidence: 99%